Święty Józef jako opiekun Jezusa i małżonek Maryi według Orygenesa - Grzywaczewski, Jozef (Vox Patrum, 2019)
The author of the article presented the most important points of Origen’s teaching on Saint Joseph. It is to be noticed that there is no josephology in the contemporary sense of this term. As matter of fact, Origen was not interested in Joseph’s person; he spoke about him while speaking about Christ and Mary, and about the Virginal conception of Jesus. In the center of Origen’s thoughts was the Divine Logos who accepted the human nature for the people’s salvation. Origen decided to write something on Joseph because of the satirical stories propagated by the enemies of Christianity; Celsus was the most famous among them. Some anti-Christian polemists proclaimed that Jesus was Joseph’s son, some others said that He was conceived within an illegal union of Mary with a stranger; they invented his name (Panthera). There were people who declared that Joseph and Mary had had sexual relations after the birth of Jesus; the persons called brothers and sisters of Jesus were apparently born from such a union. In such circumstances Origen started to refute the false stories and to present the Gospel’s teaching on Jesus Christ, on His Mother Mary and on Joseph. Origen underlined that Joseph was Mary’s husband, but not in the common sense of this word.